Portadores de vitiligo: estudo das emissões otoacústicas e efeito de supressão - Angrisani, Rosanna Mariangela Giaffredo (2009)
Vitiligo is a skin disease characterized by absence of melanin due to melanocytes destruction. AIM: to study the incidence of hearing alterations in patients with vitiligo. METHOD: prospective audiological evaluation, transient-evoked otoacoustic emission recordings and study the effects of suppression in 24 patients with vitiligo. Their ages ranged from 15 to 45 years. RESULTS: 21 patients (87.5%) had normal audiometry; 2 had unilateral hearing loss in the high frequencies and 1 had cochlear moderate hearing loss in the left ear. Of these 21 subjects, 66.7% had no otoacoustic emissions, suggesting cochlear dysfunction. Only 7 patients had otoacoustic emissions present in all frequencies (29.2%) and 17 (70.8%) did not have them, and the highest rate of no otoacoustic emissions happened in the right ear of males. Regarding the suppression study, 6 subjects failed, all of them were females, and their left ears were the most affected. CONCLUSION: the findings show that patients with vitiligo, particularly males, have a greater predisposition to cochlear dysfunction, especially in the right ear. As far as the suppression effect was concerned, there was a greater alteration in the female efferent system, particularly in the left ear. Hearing alterations did not vary as far as age is concerned, type of vitiligo and time of disease progression.